ENGINEERING CALCULUS - Noorwirdawati Ali; Sharifah Salwa Mohd Zuki; Faisal Sheikh Khalid (Penerbit UTHM, 2025)
Calculus is a fundamental pillar of engineering mathematics, providing the essential tools to model, analyze, and solve real-world problems. This book, designed specifically for engineering students, aims to offer a comprehensive and intuitive introduction to the principles of calculus. Structured to enhance understanding and promote active learning, the book begins with differentiation, gradually building upon basic functions and advancing to more complex rules and techniques. Students will find a clear progression through chapters, covering topics such as the differentiation of parametric and implicit functions, logarithmic differentiation, and the application of differentiation to rates of change and curve analysis. Integration, another cornerstone of calculus, is treated with the same step-by-step approach, exploring both indefinite and definite integrals and offering various techniques for solving them, such as substitution, integration by parts, and partial fractions. We then delve into the application of integration in engineering contexts, calculating areas, surface revolutions, arc lengths, and curvature. Finally, the book introduces first-order differential equations, focusing on their formation, solution techniques, and applications in engineering scenarios like linear motion. Each chapter is supplemented with illustrative examples and exercises designed to reinforce concepts and encourage problem-solving skills. This book is designed to not only teach the principles of calculus but also to highlight its practical significance and versatility in engineering. By working through the examples and exercises, students will develop a solid understanding of the material and gain confidence in applying calculus to solve engineering problems. It is my hope that this book serves as a valuable resource, helping students build a strong mathematical foundation that will support their academic and professional growth.